The Flemish movement : a documentary history 1780-1990 - Hermans, Theo; Vos, Louis, 1945-; Wils, Lode (Bloomsbury academic collections. History. European history., 2015)
This documentary history of the Flemish movement and its role as a social, intellectual and political force in Belgium recounts the struggle for the recognition of the language and cultural identity of the Dutch-speaking inhabitants of Belgium.